2011
DOI: 10.1093/heapol/czr074
|View full text |Cite
|
Sign up to set email alerts
|

Perceived quality of and access to care among poor urban women in Kenya and their utilization of delivery care: harnessing the potential of private clinics?

Abstract: This paper uses data from a maternal health study carried out in 2006 in two slums of Nairobi, Kenya, to: describe perceptions of access to and quality of care among women living in informal settlements of Nairobi, Kenya; quantify the effects of women's perceived quality of, and access to, care on the utilization of delivery services; and draw policy implications regarding the delivery of maternal health services to the urban poor. Based on the results of the facility survey, all health facilities were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 28 publications
7
57
0
Order By: Relevance
“…friendliness and respectfulness of staff, facility amenities, etc.). This is consistent with other research from the Nairobi slums, which demonstrates that women perceive the quality of care to be highest at the small, private (often unlicensed) maternity facilities, which are often unequipped technically to provide safe deliveries but which offer kinder, more respectful care and more comfortable amenities (Fotso and Mukiira, 2012). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…friendliness and respectfulness of staff, facility amenities, etc.). This is consistent with other research from the Nairobi slums, which demonstrates that women perceive the quality of care to be highest at the small, private (often unlicensed) maternity facilities, which are often unequipped technically to provide safe deliveries but which offer kinder, more respectful care and more comfortable amenities (Fotso and Mukiira, 2012). …”
Section: Discussionsupporting
confidence: 90%
“…A large number of public, private and mission facilities offer antenatal care (ANC) and delivery services in Nairobi, with wide variation in the quality of services (National Coordinating Agency for Population and Development, Fotso and Mukiira, 2012, Ziraba et al, 2009). We define “active” ANC patients as women who switch providers over the course of their pregnancy and analyze the characteristics and health seeking behavior of these patients, exploring whether active patients appear to be seeking and receiving a different level of quality than “non-active” patients (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a high perceived quality of care is associated with an increased utilization of services and therefore acceptability. 31 The PCAS measures caregivers' perceptions of the quality of primary care through 10 different domains, including detailed measurement of the providerpatient relationship (communication quality, patient trust, provider knowledge of patient, interpersonal treatment, and relationship duration). For this study, we have grouped these 10 domains into three general categories of accessibility, clinical care, and patient relationships ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…However, an increasing number of people in developing countries now live in urban areas. Few of these large cities are able to provide their rapidly growing populations with the appropriate health care, which often results in increased levels of urban poverty and ill health [15]. While we are gaining insight in the use of CAM in developed countries, the use of herbal medicine or other forms of TM among urban populations in developing countries is poorly documented [12].…”
Section: Introductionmentioning
confidence: 99%